PEG-assisted microwave hydrothermal growth of spherical mesoporous Zn-based mixed metal oxide nanocrystalline: Ester production application - Soltani, Soroush; Khanian, Nasrin; Thomas, Shean Yaw Choong; Rashid, Umer, Umer; Arbi Nehdi, Imededdine; Mohamed Alobre, Mohsen (Elsevier BV, 2020)
In the present research, various spherical mesoporous ZnO-based nanocrystalline(ZnAl2O4, CuO-ZnO, TiO2-ZnO) were synthesized via post-calcination treatment at 600 °C for 4 h over N2 flow gas, which initially went through a simple PEGassisted microwave hydrothermal route by adapting the varieties of PEG (i.e. PEG 2000, PEG 4000, PEG 6000, PEG 10000, and PEG 20000) using incomplete carbonized glucose (ICG) as a template. The as-synthesized mesoporous ZnObasednanocrystallineswere further characterized by mean of XRD, N2 adsorption and desorption, NH3-TPD, FESEM, and EDX. The experimental outcomes revealed that the extent of PEG 6000 in mixture played the vital role in the growth of spherical mesoporous ZnO-based nanocrystallines compared to other PEG molecular weights. The N2 adsorption and desorption data confirmed the mesopore structure of the samples, possessing the specific surface areas in the range of 450.35–592.55 m2 g−1. By verifying the optimum PEG-assisted microwave hydrothermal conditions, one-pot polymerization of poly(sodium4-styrenesulfonate) was employed to activate surface areas and mesopore walls by -SO3H functional groups using for ester productionthrough transesterification of used cooking oil, resulted in methyl ester content of 97.4% and excellent reusability for ten sequential reactions withoutanyfurtherregeneration. Moreover, biodiesel quality evaluation analysis showed that the prepared methyl ester satisfied both EN (14214) and ASTM (D6751) specifications.